Kinetic and Equilibrium Parameters of Erythromycin Sorption on Various Sorbents - N. V. Kotova (Антибиотики и Химиотерапия, 2020)
Optimal conditions for erythromycin sorption on supercoupled isoporous Purolight sorbents (styrosorbs) S-106, S-150 and S-160 and on macroporous sulfocation exchanger KU-23 were determined. High selectivity of erythromycin sorption on the supercoupled isoporous cation exchanger S-106 was shown, that was evident from the high distribution coefficient. The effective diffusion coefficient on the cation exchanger S-106 was higher by a factor of 102 (1.1X10-11 m2/s) that was in favour of a comparatively high diffusion rate.